16th IHIW: A Website for Antibody‐Defined HLA Epitope Registry. (9th November 2012) - Duquesnoy, R. J.; Marrari, M.; Sousa, L. C. D. da M.; Barroso, J. R. P. de M.; Aita, K. M. de S. U.; da Silva, A. S.; do Monte, S. J. H.
The concept that HLA antibodies are specific for epitopes rather than HLA antigens is important not only for the determination of mismatch acceptability for sensitized patients but also for a better understanding of the antibody response to an HLA mismatch. Numerous publications describe epitope‐specific antibodies, but there is no standardized information about the repertoire of clinically relevant HLA epitopes. Under auspices of the 16th IHIW, we have developed a website‐based registry of antibody‐verified HLA epitopes. Epitope notations are based on HLA molecular modelling of amino acid residues in polymorphic sequence positions. Informative epitope‐specific antibodies had been induced by a transplant, transfusion or pregnancy and were monoclonal antibodies or eluates of sera absorbed with single HLA alleles. Antibody reactivity was determined in binding assays with single‐allele panels. Antibody producer/immunizer HLA types enhanced the characterization of specific epitopes. The Registry also includes epitopes described in original research publications. Based on the extent of antibody reactivity information, we assigned epitope status as confirmed (well documented) or provisional (more data are needed). At present, the Registry has 69 HLA‐ABC, 53 DRB1/3/4/5, 17 DQ, 8 DP and 22 MICA antibody‐verified epitopes and will be updated on a quarterly basis. Laboratories worldwide continue to submit data about previously unreported antibody‐specific epitopes. For each epitope, the website shows its amino acid composition and HLA alleles that share the epitope. Links show antibody reactivity patterns, sensitization information and references. Other links show molecular modelling of corresponding structural epitopes and polymorphic residue information for epitope‐carrying alleles. The website will also have a link to epitope frequency information in different populations. Search functions will list mismatched epitopes on mismatched alleles for selected HLA types. The HLA Epitope Registry will become a valuable resource for researchers interested in HLA compatibility at the epitope level and investigating antibody responses to HLA mismatches.